Association between Dose and Duration of Cisplatin Exposure with Sitotoksisity Effect on Nasopharyngeal Carcinoma Stem Cell - Widodo Ario Kentjono1, Lakshmi Kusuma Wardhani1, Achmad C Romdhoni1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Nasopharyngeal carcinoma (NPC) is ranked 6th of malignant tumors in Indonesia, while cisplatin is an effective chemotherapy therapy but the side effects and resistance problems are two major constraints limiting its application. Objective: To analyze the correlation of dose and duration of cisplatin exposure with cytotoxic effects on nasopharyngeal carcinoma stem cells Methods: A true experimental laboratory in vitro with the factorial design was used in this study. The biopsy NPC tissue was cultured and processed to obtain NPC stem cells to be treated with cisplatin exposure at different doses (0.05, 0.1, 0.2, 0.4, 0.8, 1 and 2 ?g) and different durations (24 and 48 hours). The number of dead cells after exposure will be calculated using a hemocytometer after 24, 48, and 72 hours of NPC stem cells free of cisplatin. Results: Death stem cell density of NPC was mostly obtained at the exposure of 2 ?g/ml cisplatin dose after 24 hours observation was 81.37%, while the smallest death cell density a dose of 0.05 ?g/ml after a 72-hour observation was 21.3%. Statistical analysis with multiple regression correlation tests between the density of death cell and cisplatin dose was obtained the coefficient correlation 0,827 and value p = 0,000. The analysis of the correlation between cisplatin exposure duration and death cell was also significant with the correlation coefficient -0.357 and the value p = 0.001. The cutoff point that correlated the dose and death stem cell of NPC by 50% in both 24 and 48 hours of exposure was 1 ?g (EC50). Conclusion: There was a correlation between the increased dose of cisplatin with the cytotoxicity effects on NPC stem cell.